Risk factors, biochemical markers, and genetic polymorphisms in early coronary artery disease - Izar,Maria Cristina (2003)
OBJECTIVE: To assess the risk factors, lipid and apolipoprotein profile, hemostasis variables, and polymorphisms of the apolipoprotein AI-CIII gene in early coronary artery disease (CAD). METHODS: Case-control study with 112 patients in each group controlled by sex and age. After clinical evaluation and nutritional instruction, blood samples were collected for biochemical assays and genetic study. RESULTS: Familial history of early CAD (64 vs 39%), arterial hypertension (69 vs 36%), diabetes mellitus (25 vs 3%), and previous smoking (71 vs 46%) were more prevalent in the case group (p<0.001). Hypertension and diabetes were independent risk factors. Early CAD was characterized by higher serum levels of total cholesterol (235 ± 6 vs 209 ± 4 mg/dL), of LDL-c (154 ± 5 vs 135 ± 4 mg/dL), triglycerides (205 ± 12 vs 143 ± 9 mg/dL), and apolipoprotein B (129 ± 3 vs 105 ± 3 mg/dL), and lower serum levels of HDL-c (40 ± 1 vs 46 ± 1 mg/dL) and apolipoprotein AI (134 ± 2 vs 146 ± 2mg/dL) [p<0.01], in addition to an elevation in fibrinogen and D-dimer (p<0.02). The simultaneous presence of the rare alleles of the APO AI-CIII genes in early CAD are associated with hypertriglyceridemia (p=0.03). CONCLUSION: Of the classical risk factors, hypertension and diabetes mellitus were independently associated with early CAD. In addition to an unfavorable lipid profile, an increase in the thrombotic risk was identified in this population. An additive effect of the APO AI-CIII genes was observed in triglyceride levels.